Identifikasi Karakter Fenotip Daun Tanaman Aren (Arenga pinnata Merr) di Kabupaten Tapanuli Selatan - Parmanoan Harahap; Mahyuni Khairiyah Harahap; Fitra Syawal Harahap (Jurnal Pertanian Tropik, 2019)
Identification Phenotypic Character of the Leaves Palm Plant in South Tapanuli Regency This studyaims to determine the effect of the phenotype character of palm leaf leaves on the production of roomiein wild populations of natural habitats in South Tapanuli Regency. The study was conducted in fivevillages in each oft he four sub-districts in the South Tapanuli district. Two hundred sugar palm plantsoriginating from four natural habitats have been identified in accordance with plant identificationprocedures issued by the IPGRI (International Plant Genetic Resources Institute, 1995) and analyzed.The results show that 4 clusters were formed with 75% similarity or 25% diversity. These results canbe concluded that cluster 1 is the population of palm plants that have the long character of petioleand the highest number of unproductive leaves. Whereas the characters of leaf length and rachis lengthare still lower than the population of sugar palm plants in cluster 4. Cluster 2 is the population of sugarpalm plants that has the highest character of sap production per day. Cluster 3 is a population ofpalm plants that have the highest leaf width character. Cluster 4 is a population of palm plants thathave the highest leaf length and rachis length with the highest number of leaflets and the largest rachiscircumference and petiole circumference. The number of productive leaves and the percentage of sapsugar content above average.